Microfluidic radiosynthesis of [18F]FEMPT, a high affinity PET radiotracer for imaging serotonin receptors - Collier, Thomas Lee; Liang, Steven H.; Mann, J. John; Vasdev, Neil; Kumar, J. S. Dileep (Beilstein Journal of Organic Chemistry, 2017)
Continuous-flow microfluidics has shown increased applications in radiochemistry over the last decade, particularly for both pre-clinical and clinical production of fluorine-18 labeled radiotracers. The main advantages of microfluidics are the reduction in reaction times and consumption of reagents that often result in increased radiochemical yields and rapid optimization of reaction parameters for 18F-labeling. In this paper, we report on the two-step microfluidic radiosynthesis of the high affinity partial agonist of the serotonin 1A receptor, [18F]FEMPT (pKi = 9. 79; Ki = 0.16 nM) by microfluidic radiochemistry. [18F]FEMPT was obtained in ≈7% isolated radiochemical yield and in >98% radiochemical and chemical purity. The molar activity of the final product was determined to be >148 GBq/µmol (>4 Ci/µmol).
Keywords: agonist; fluorine-18; 5-HT1A; microfluidics; PET